A Study to Assess the Health-Related Quality of Life (HRQoL) in Children with Overweight and Obesity in selected community area, Chennai - Tamilselvi. D,; Dr. Sathiyalatha Sarathi,; Dr. V. Hemavathy, (The Bioscan, 2025)
Introduction: Health-Related Quality of Life (HRQoL) in children experiencing overweight and obesity is a multifaceted issue influenced by various psychosocial, physical, and emotional factors. Aim of the study: The main aim of the study to assess the Health-Related Quality of Life (HRQoL) in Children with Overweight and Obesity in selected community area, Chennai. Methodology: This study adopted a descriptive design to assess the Health-Related Quality of Life (HRQoL) among children with overweight and obesity in a selected community area of Chennai. A total of 80 children aged 6 to 12 years were selected using a convenience sampling technique through local schools. Children who met the criteria for overweight or obesity based on age- and sex-specific BMI percentiles were included, while those with medical conditions affecting growth or HRQoL were excluded. Result: The study findings revealed that 56.25% of the children were overweight and 43.75% were obese, with a mean BMI of 23.6 ± 3.1 kg/m². The overall HRQoL score was 66.7 ± 11.5, indicating a moderate quality of life. Among the domains, social functioning scored highest, while school functioning was lowest. Categorically, 55% of the children had moderate HRQoL, 27.5% low, and only 17.5% high, suggesting a notable impact of excess weight on children’s well-being. Conclusion: The study concludes that overweight and obesity significantly affect the health-related quality of life (HRQoL) in children, particularly in emotional and school functioning.